Bio-rational management of whitefly (Bemisia tabaci) for suppressing tomato yellow leaf curl virus (Bangladesh Journal of Agricultural Research, 2016)
Whitefly (Bemisia tabaci) is the vector of tomato yellow leaf curl virus (TYLCV), is a serious pest of vegetables and other crops worldwide. The experiment was conducted at Bangladesh Agricultural Research institute (BARI) during two consecutive years of 2009 and 2010 to select a suitable bio-rational management practice against white fly, transmitting TYLCV. Treatments comprising tomato variety Ratan with diseased plant uprooting, spraying admire, applying admire on trap crop (marigold), spraying neem, sesame and mustard oil with trix and the untreated control were used in this experiment. The variety Opurba with similar materials as described above was used. Percent virus infected tomato plants ranged from 1.33 to 19.00 in two consecutive years, where the highest infection was recorded in control plot with variety Opurba and the lowest was recorded in variety Ratan treated with Admire. Consequently, the highest yield (47.70 and 52.36 t ha-1 in 1st and 2nd year, respectively) in the plots of variety Ratan treated with admire and the lowest yield was recorded in untreated control plots with variety Opurba (14.75 and 30.30 t ha-1) for the two consecutive years. A strong positive correlation was observed between whitefly population and % TYLCV infection for both the years and both varieties of tomato. While a negative correlation was observed between % TYLCV infection with number of fruits plants-1 and yield (t ha-1) for both the years and in both varieties of tomato. These results are consistent with the occurrences of TYLCV, which have been associated with the percent virus infection in relation to yield and yield contributing characters of tomato.Bangladesh J. Agril. Res. 41(4): 583-597, December 2016